Colonoscopy in patients aged 80 years or older and its contribution to the evaluation of rectal bleeding. Issue 799 (May 1992) - Bat, L.; Pines, A.; Shemesh, E.; Levo, Y.; Zeeli, D.; Scapa, E.; Rosenblum, Y.
Abstract : Colonoscopies performed in patients aged 80 years or older at the Sheba Medical Center were analysed according to the primary indication for the procedure: 101 colonoscopies were performed because of rectal bleeding of at least 2 months duration, and 335 for all other indications. Carcinoma of the large bowel was found in 29 (28.7%) bleeders, with the rectum being the most frequently involved site (12 patients). Among the non-bleeders, the prevalence of cancer was significantly lower (33 cases, 9.8%; P less than 0.001), and rectal carcinoma was less common (five patients, P = 0.04), but proximal tumours were more frequent. Of patients with cancer who had operations, the majority (72%) had a tumour confined to the bowel wall (Dukes A or B). The rate of adenomas was similar for both groups (34% vs 29%). The non-bleeders complained more frequently of abdominal pain or a change in bowel habits as compared to the bleeders, but both groups had similar rates for anaemia and weight loss. In all, 47% of these octogenarians with cancer, and 26% with adenomas were referred for colonoscopy because of rectal bleeding. This procedure was found to be safe in old age, as we recorded only four (0.9%) non-fatal complications among our series, a similar figure to the overall incidence of complications at our Institute. In conclusion, our data indicate that rectal bleeding in octogenarians warrants a complete colonic investigation, preferably by total colonoscopy.